Supplemental Cardioplegia Immediately before Graft Implantation may Improve Early Post-Transplantation Outcome - Tevaearai Stahel, Hendrik T.; Unger, Darja; Schmidli, Juerg; Gahl, Brigitta; Englberger, Lars; Kadner, Alexander; Eberle, Balthasar; Mohacsi, Paul; Carrel, Thierry P. (Frontiers in Surgery, 2014)
Background: Preservation of cardiac grafts for transplantation is not standardized and most centers use a single administration of crystalloid solution at the time of harvesting. We investigated possible benefits of an additional dose of cardioplegia dispensed immediately before implantation. Methods: Consecutive adult cardiac transplantations (2005–2012) were reviewed. Hearts were harvested following a standard protocol (Celsior 2L, 4–8°C). In 2008, 100 ml crystalloid cardioplegic solution was added and administered immediately before implantation. Univariate and logistic regression analyses were used to investigate risk factors for post-operative graft failure and mid-term outcome. Results: A total of 81 patients, 44 standard (“Cardio−”) vs. 37 with additional cardioplegia (“Cardio+”) were analyzed. Recipients and donors were comparable in both groups. Cardio+ patients demonstrated a reduced need for defibrillation (24 vs. 48%, p = 0.03), post-operative ratio of CK-MB/CK (10.1 ± 3.9 vs. 13.3 ± 4.2%, p = 0.001), intubation time (2.0 ± 1.6 vs. 7.2 ± 11.5 days, p = 0.05), and ICU stay (3.9 ± 2.1 vs. 8.5 ± 7.8 days, p = 0.001). Actuarial survival was reduced when graft ischemic time was >180 min in Cardio− but not in Cardio+ patients (p = 0.033). Organ ischemic time >180 min (OR: 5.48, CI: 1.08–27.75), donor female gender (OR: 5.84, CI: 1.13–33.01), and recipient/donor age >60 (OR: 6.33, CI: 0.86–46.75), but not the additional cardioplegia or the observation period appeared independent predictors of post-operative acute graft failure. Conclusion: An additional dose of cardioplegia administered immediately before implantation may be a simple way to improve early and late outcome of cardiac transplantation, especially in situations of prolonged graft ischemia. A large, ideally multicentric, randomized study is desirable to verify this preliminary observation.